Fault and load flows analysis of electricity transmission and distribution system in Casanare (Colombia) (2017)
This article describes a simulation of the electrical local distribution and regional transmission system of Enerca S.A. E.S.P. at 34.5 kV and 115 kV, identifying the most critical circuits and substations. The company is located in one of the major petroleum production areas in Colombia, and because of a massive growth in this sector, the electrical company expanded its networks in a radial way. This expansion was improvised and poorly planned due to the accelerated need to meet the new demand, which resulted in stability, balance, voltage regulation, and system reliability problems. Load flow and fault analyses were carried out based on current load and demand predictions in the short and medium term. Twelve proposals were made for network and substation modernization that once implemented will significantly improve the service reliability.